Implementasi SMED: Perbaikan Waktu Changeover Part pada Line Produksi Seat di PT. Selamat Sempurna, Tbk - Rahayu, Puji; Supono, Joko; Anisa, Nur (Journal Industrial Manufacturing, 2021)
PT. Selamat Sempurna, Tbk is a company that manufactures  automotive parts, namely car filters. This filter product has many part numbers. In this company has one of the production lines, namely Line Seat Press Shop, this line produces components from filters, namely seat components. Seat is the main part of the filter component that functions as a filter holder to the engine. This Seat component consists of several part numbers (shapes or variations) following the filter product, and some part numbers handled by the manual engine B070 & L224 will affect the changes in the production engine settings. This production machine includes machines that require time in a slow setup process for switching dies when switching from one part number to another part number compared to other machines, because the element of the process setting is long. With a fishbone diagram, the root cause of the Change Over Part long problem on the machine is from the method category (there is no preparation desk dies and there is not separation of external setup and internal setup). Previously the time needed for Change Over Part was 1961 seconds. After knowing the root cause of the problem and the improvement of the time needed is only 866 seconds. The time difference is 1067 seconds, so save on average time 1095 seconds or 18 minutes / setup. Keywords: Filter product, Change Over part (COP), Fishbone Diagram, Setup, Process Elements.